Metabolic Syndrome Components in Patients with Pituitary Adenoma - Gonzalez-Almazan, Jorge A.; Cortes-Contreras, Ana Paula; Flores-Rabasa, Regina; Mendez-Garcia, Lucia A.; Escobedo, Galileo; Navarro Olvera, José L.; Carrillo-Ruiz, José D. (Hormone and Metabolic Research, 2023)
Pituitary adenomas are benign tumors of the anterior portion of the pituitary gland (adenohypophysis), representing the 25% of all the tumor alterations. Pituitary adenomas are classified by the type of hormone secreted, cellularity, size, and structural alterations by the hormonal segregation. The diagnosis consists on the histopathological identification of cell types and the image-guided by magnetic resonance or tomography; the treatment can be both pharmacological and surgical. Metabolic Syndrome is the set of clinical conditions that increase the risk of cardiovascular diseases with an estimated prevalence of 25% worldwide. The alterations of metabolic syndrome are obesity, hypertension, dyslipidemia, insulin resistance, and diabetes mellitus type II. Pituitary adenomas and metabolic syndrome have an important relationship, hormone-secreting by pituitary adenomas affects a myriad of signaling pathways, which allows a favorable environment for the appearance of the metabolic syndrome. Moreover, patients with pituitary adenomas are shown to have an improvement in metabolic parameters after the medical/surgical treatment. The objective of this review is to explore the possible mechanisms through which PAs contributes to MetSx.
Keywords: pituitary adenoma; metabolic syndrome; insulin resistance; hypertension; obesity